Pengaruh Penerapan Strategi Relating, Experiencing, Applying, Cooperating Dan Trasferring (REACT) Terhadap Pemahaman Konsep Matematis Peserta Didik Kelas XI MIPA SMA Adabiah 2 Padang - Silvia Mayang Sari (Jurnal Edukasi dan Penelitian Matematika, 2020)
One goal of mathematics learnings understanding mathematical concepts that are expected to be owned by students. But the reality is that in Adabiah 2 Senior High School Padang is still not optimal or still low. Learning strategies have not been able to improve the concepts of students. If understanding the concept is low, it will affect other mathematical abilities. The purpose of this research is and to know and describe whether the understanding of the concepts of students who learn with REACT strategies is better than understanding the concepts of students who learn with direct learning models in class XI MIPA SMA Adabiah 2 Padang and to know and describe the improvement in understanding of the concepts of learners who learn with REACT strategy. This type of research is quasy experiment and descriptive research design with Randomized Control Group Design. The population is class XI MIPA Adabiah 2 Padang High School with research samples namely class XI MIPA 1 and XI MIPA 2. Research instruments in the form of quizzes and concept understanding tests. Data on the development of this ability is described through quiz results, while the test results are analyzed by t-test. Based on the quiz results obtained that the development of conceptual understanding increased with the REACT strategy, and based on the results of the test analysis it was found that the real level of α = 0.05 t-test obtained P-value = 0.00 because P-value < α, then H0 was rejected . This means that understanding the concepts of students who learn with REACT strategies is better than understanding the concepts of students who learn by direct learning models in class XI MIPA Adabiah 2 Padang High School in 2019/2020 Academic Year.Keywords – Mathematical Concept Understanding, REACT Strategy.